COVID-19 and Dermatologist: A Scenario from Nepal - Thapa, Deeptara Pathak; Paudel, Vikash (Nepal Journal of Dermatology, Venereology & Leprology, 2021)
Corona virus disease-2019 (COVID-19) had impacted the healthcare sector severely. The impact of pandemic had a foothold even on dermatology practice and dermatology residency teaching programs. Patients with dermatological diseases, few diseases arising due to COVID-19 and patients with immunosuppressive for chronic dermatological conditions were affected. In the midst of this pandemic, all dermatologist should learn and contribute to the mankind with precaution at all level either in healthcare or society.